Glass Core Pendants from the Museum of the Studium Biblicum Franciscanum - Jerusalem - Lisella, A.R. (Liber Annuus, 2005)
Abstract A group of polychrome glass pendants from the Museum of the Studium Biblicum Franciscanum is published here for the first time. It represents an updating of M. Seefriedʼs work, “Les pendantifs en verre sur noyau des pays de la Méditerranée antique”. Seven polychrome glass pendants, four of which are polychrome glass animal figurines and four small glass heads, are studied here. They can be classified in the following manner: A – demon heads -, B3 – male heads with twisted hair style -, B4 – double-faced heads -, C2 – the male heads with curly hair -, D2 – female heads. The animal figurines are classified by Seefried as type E, which includes the animal representations. Finally, the group of the four small heads, different from the type identified by Seefried, represent the head of the hat-pins or of the small stick for the make-up known both in the East and in the West, especially in the burial equipments dating back to imperial Rome.